Violence and illegal economic activity: a deconstruction - Naylor, Robin T. (Crime, law and social change, 2009)
Obviously there is nothing new about humans using violence as a tool to advance their economic, political and social interests. There is no lack of quick and superficially convincing reasons on offer, reflecting the political agenda of those doing the offering. However sensible explanations of complex social phenomena are inevitably messy. Rather than yielding absolute certainty, they can at best indicate tendencies constrained by circumstances that are subject to dramatic change through random shocks of both exogenous and endogenous origin. This paper examines the possible role played by violence in contemporary illegal-market activity in an effort to clear up definitional ambiguities and highlight the underlying logic or lack thereof in frequent claims about a close association between earning, spending, saving or investing of ill-gotten gains and any propensity that participants might have to advance or defend their economic interests by violent means. It concludes that the links are at best tenuous and confined only to marginal instances that are usually explicable by the broader social, political and cultural context rather than anything inherent in the logic of these markets.